SUPPLY CHAIN ANALYSIS OF RAW MATERIAL AVAILABILITY IN FAST FOOD INDUSTRY OF MCDONALD’S MALANG - Felicia Anggawinata (AIBPM Publisher, 2018)
This research is important to understand how supply chain management, especially related to the supply of raw materials in the food and beverage industry, specifically in international franchising companies. This paper contains a study of supply chain management at the international franchise company